Salman Rushdie’s The Enchantress of Florence as History Reinvented - Adhikari, Tara Prasad (Literary Studies, 2016)
The present paper focuses on how Rushdie blurs boundary between history and stories in his famous novel The Enchantress of Florence and what end does he achieve. Salman Rushdie’s fascination with history becomes evident in his novel The Enchantress of Florence. It seems that Rushdie is truly handcuffed to history. In this novel, he has mixed history and legend in order to recreate new myths and histories. The novel chooses to combine myth and history, fact and fiction in order to liberate history from the shackles of positivism and re-invent it. This mixing of the real with the fictional and the fusion of the mythical with the historical has not only enriched his novels but has also opened up a new avenue for reading and writing history differently.